Doing (Prison) Research Differently: Reflections on Autoethnography and ‘Emotional Recall’ - Luigi Gariglio (Oñati Socio-Legal Series)
This paper offers a reflection on both the family of methods called autoethnography and on the experience of doing autoethnography in practice as a follow-up to a prison ethnography. By engaging with the literature on autoethnography, it provides an overview of the methodology and focuses on one particular experience of doing (prison) research differently by adopting the notion of emotional recall as a heuristic tool. More specifically, this paper shows how emotional recall was vital to yielding a substantive research finding through autoethnographic re-engagement with data collected during an ethnography of prison officers’ threat of the use of force in an Italian prison. Through autoethnography, prison officers’ favouritism towards Mafioso was found to be a key aspect of officers’ use of discretion in the prison setting.